Synthesis and antimicrobial testing of 3-amino-3-deoxy-1,2,5,6-di-isopropylidine-a-D-allofuranose - Martinez, Angelica R. (Animo Repository, 1995)
A new method for the synthesis of 3-amino-3-deoxy-1,2:5,6-di-O-isopropylidene-alpha-D-allofuranose is described. This reaction sequence consists of esterifying 1,2:5,6-di-O-isopropylidene-alpha-D-glucofuranose (diacetone glucose) with trifluoromethanesulfonic (triflic) anhydride, reacting the resulting trifluoromethanesulfonate (triflate) with sodium azide in the presence of 18-crown-6 with DMF as the solvent and reducing the azido sugar with LiAIH4. This process for the formation of amino sugar is fast, mild and convenient. It does not experience the difficulties such as decomposition and lack of reactivity at the secondary carbon which is usually encountered in substitution reactions involving diacetone glucose. In addition, the biological activity of the synthesized azido and amino sugars against a gram (-) and gram (+) bacteria is tested. The azido sugar is active against both, while the amino sugar is active against the gram (-) bacteria.